I'm from - Gray, Gary (Gary R.), Jr (Balzer + Bray, an imprint of HarperCollins Publishers, 2023)
"Early morning wakeups and homemade pancakes, raucous bus rides and schoolyard games, family games and bedtime rituals... These are the small moments that shape a child's day. I'm from is an invitation into the vivid world of one small boy, a poetic account of all the people and places and things that shape who he is and define where he is from" --